INFLUENCE OF ELECTRIC VOLTAGE ON GERMINATION OF LEGUMINOUS SEEDS - Mamlić, Zlatica J; Nikolić, Zorica; Mandić, Gordana; Mamlić, Goran; Đukić, Vojin; Katanski, Snežana; Uhlarik, Ana (Journal of Agricultural Sciences (Belgrade), 2021)
The aim of this paper was to examine the influence of electrostatic field on seeds of soybean (Glycine max L), vetch (Vicia spp. L.), pea (Pisum sativum L.), grass pea (Lathyrus sativus L.) and chickpea (Cicer arietinum L.) which was selected at the Institute of Field and Vegetable Crops in Novi Sad.  Used DC voltage is 9V. Seed treatment times were 0 (control), 1, 2 and 3 minutes. A switch is placed between one electrode and the battery terminal so that the circuit between the mentioned electrodes can be interrupted at any moment, and between which seeds are placed, which are subjected to treatments. During the experiment, the voltage values were monitored, in order to determine whether the electrostatic field between the electrodes constant, i.e. invariable over time. After treatment, seed quality was examined using a germination test (optimal temperature) and a cold test (low temperature). The results of the study showed that the effect of the electrostatic field on seed quality depended on the plant species, the time of seed treatment and the temperature conditions in which the seed germinated after treatment. The increase in germination energy ranged up to 18.18% in legumes, and a decrease of up to 12% in chickpea. The application of electrostatic field had a significantly greater impact on seeds that were exposed to low temperatures in the germination process after treatment. The increase in seed germination ranged up to 82.35% in chickpeas, and the decrease to 92.68% in peas. In addition, the obtained results indicate that it is not possible to talk about the universal application of a certain treatment time, because it can happen that it does not correspond to a certain plant species, so the quality of seeds can deteriorate.            Keywords: electrostatic field, cold test, germination, legumes